Equilibrium and kinetic studies on the adsorption of lead and copper in aqueous solution on coco peat - Parcon, Michelle Rose R.
Previous studies on the adsorption of lead and copper on coco peat show that coco peat can effectively bind these metal ions. However, these studies have not investigated the effect of pH and the presence of other ions on equilibrium and kinetic data. This study addressed that research gap by performing equilibrium and kinetic studies at different pH, and on single and binary-solute systems. The equilibrium data fitted satisfactorily to Languir isotherm indicating monolayer adsorption for lead and copper. An increase in pH leads to consequent increase in the monolayer adsorption capacities of lead and copper. Competition for adsorption sites between ions decrease the adsorption capacities of both metals. kinetic data fitted well to pseudo-second order kinetic model which means that the rate-limiting step in the adsorption of lead and copper on coco peat is chemisorption. Increasing the pH of the solution leads to an increase in the initial sorption rate. Due to competitive sorption, the initial sorption rate is lower in a binary-solute system compared to a single-solute system.